Design and construction of a combustion system for a high-density polyethylene pyrolytic reactor (Revista Cientifica Ingenio Magno, 2024)
The research aims to design and construct a liquefied petroleum gas (LPG) burner for the pyrolysis of high-density polyethylene waste. Using a quantitative and experimental methodology, theoretical concepts were reviewed, and the combustion equipment was developed. Its performance in terms of efficiency and emissions will be evaluated during its operation in a pyrolytic reactor. The project aims to reduce pollutant and greenhouse gas emissions, offering a clean alternative to produce synthetic fuels from the thermal decomposition of polymers. This research addresses the question: To what extent are greenhouse gas (GHG) emissions reduced with the implementation of LPG as fuel in a laboratory-scale pyrolytic reactor? The introduction of LPG as an alternative fuel option in the pyrolysis process contributes to the proposal of alternative energies in the search for utilizing available resources to reduce environmental impact while employing appropriate technologies.
Keywords: Emissions; Plastic Pyrolysis; Alternative fuels; LGP Burner; Environmental sustainability